ABNORMALITAS SPERMATOZOA SEMEN SEGAR KAMBING DENGAN PEMBERIAN PAKAN SUPLEMEN EKSTRAK KUNYIT - Sitepu, Sukma Aditya; Marisa, Julia; Farid, Muhammad Miftah (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
The quality of the fresh semen of goats relates to the feed given to goat bucks. One of the herbal ingredients that can improve the quality of fresh semen is turmeric. This study aimed to determine the effect of giving turmeric extract to reduce spermatozoa abnormalities in fresh semen of goats. Observations using microscopically. The materials in this study were fresh goat semen and turmeric extract. The experimental design used in the study was a non-factorial, Completely Randomized Design with five treatments and five replications. The treatment included adding 0ml, 25ml, 50ml, 75ml, and 100ml turmeric extract. The parameter observed was the percentage of abnormal spermatozoa in fresh goats. The results showed that the addition of 0ml showed an abnormality value of 15%, 25ml = 13%, 50ml = 12%, 75ml = 12% and 100 ml = 11%. The analysis of variance showed that the results had no significant effect. They have concluded that giving turmeric extract supplements cannot reduce the value of abnormal spermatozoa in goats. The recommendation is that it is necessary to conduct further research by increasing the dose of turmeric extract in the treatment.